The engagement of mature distance students - Kahu ER; Stephens C; Leach L; Zepke N (Routledge Taylor & Francis Group, 2013)
An increasing proportion of tertiary students are aged 25 and over, and many of these students choose to study at a distance in order to more easily combine their studies with their family and work commitments. Higher attrition rates and lower course completion rates for this group highlight the need for a greater understanding of their student experience. To explore whether age and mode of study impact on student engagement, satisfaction, learning and departure intention, data from the Australasian Survey of Student Engagement from 1116 first-year undergraduate students from a single New Zealand university were analysed. Results confirm the influence of student engagement on both student satisfaction and learning, in particular the importance of a supportive learning environment. The findings suggest that while older and distance students are less likely to engage in active learning strategies with their fellow students, they have a much greater capacity to integrate their learning with their work experience. The finding that these students are as satisfied as the more traditional-aged, on-campus students suggests that their experience is different, but not second-rate. Universities need to build on the strengths of these students as well as provide greater opportunities for them to form collaborative relationships with similar students. Limitations stemming from the timing of the survey and the inherent limitations of cross-sectional surveys suggest the need for more in-depth longitudinal work to understand the changing nature of engagement for these students and to explore why they engage differently with their studies.
This is an Accepted Manuscript of an article published by Taylor & Francis in Higher Education Research and Development in 2013, available online: http://www.tandfonline.com/10.1080/07294360.2013.777036.
Keywords: Social Sciences; Education & Educational Research; EDUCATION & EDUCATIONAL RESEARCH; adult learning; distance learning; student engagement; work-integrated learning; UNIVERSITY; MOTIVATION; EDUCATION; VALIDITY; OUTCOMES; ADULTS; MODEL; TIME; NSSE; 13 Education